Developing English Literacy Skills to Promote Religious Moderation through English for Islamic Studies Programs among Indonesian Muslim Youth - Al Hakim, Muhammad Arif (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Empowerment through community service should have positive impacts across sectors, including education. Currently, strong English-language literacy among young Indonesian Muslims is considered vital for understanding and promoting moderate Islamic teachings globally. Thus, this study aims to explore the impact of empowering English education students through English for Islamic Studies programs on their English literacy skills. Three face-to-face programs were employed to depict the advantages of learning English literacy and religious moderation through English for Islamic Studies. This study reveals that the programs were significantly beneficial for them in improving their understanding of religious moderation, especially moderate Islam, by categorizing four indicators of those principles: national commitment, anti-violence, tolerance, and the accommodation of local wisdom and culture. Moreover, program participants improve their English literacy, specifically in reading and writing, by absorbing English technical terms related to religious moderation. The implication of the study was, first, that the implementation of English for Islamic Studies beneficially develops the participants’ English literacy, specifically in reading and writing skills. Second, the program content has positively influenced participants’ understanding of the principles of religious moderation within moderate Islam. It enhanced their ability to analyze religious moderation practices in their environment using four indicators of moderation.